Innovation in Agrotourism Development and Digital Marketing Approach to Encourage Purchase Interest at BPP Baubau City - Haerunianti; Hasrin (Tarjih : Agribusiness Development Journal, 2024)
Effective marketing of dragon fruit agrotourism and marketing tactics, which play a significant role in determining consumer buying interest, require innovation in agrotourism development to ensure customers are interested in purchasing. 1) Explain how innovation in dragon fruit agrotourism has increased consumer interest in making purchases; 2) Examine digital marketing tactics for dragon fruit agrotourism to boost consumer interest in making purchases. This kind of study makes use of qualitative research. The research sample consisted of 10 respondents, including owner of an agrotourism business, employee, trader in the agrotourism industry, and seven visitors or clients. Using descriptive data analysis, the 4P marketing concept was referenced. Numerous earlier studies have not reported on this research. Many fruit plant kinds and other plants promoting tourism require innovation in agrotourism development. Innovations in agrotourism development are necessary to pique consumers' interest in intense purchases; these innovations can decide how well dragon fruit agrotourism marketing works. Based on the study's findings on dragon fruit agrotourism development innovations at BPP, including applying a marketing mix comprising goods, costs, promotions, and suitable locations. The SWOT analysis of the agrotourism marketing plan reveals internal variables, including the company's strength, a wellthought-out and innovative agrotourism concept, and a key location. The company's weak point is inadequate amenities, such as playgrounds for kids and lodging. External reasons include the high number of foreign visitors and the community's popularity of dragon fruit-based economic prospects. Extreme or unpredictable weather fluctuations and perishable agricultural products pose a hazard to the firm.